2022
DOI: 10.1242/jcs.259686
|View full text |Cite
|
Sign up to set email alerts
|

PDGFR dimer-specific activation, trafficking and downstream signaling dynamics

Abstract: Signaling through the platelet-derived growth factor receptors (PDGFRs) plays a critical role in multiple cellular processes during development. The two PDGFRs, PDGFR and PDGFR, dimerize to form homodimers and/or heterodimers. Here, we overcome previous limitations in studying PDGFR dimer-specific dynamics by generating cell lines stably expressing C-terminal fusions of each PDGFR with bimolecular fluorescence complementation (BiFC) fragments corresponding to the N-terminal or C-terminal regions of the Venus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 77 publications
(73 reference statements)
3
28
0
Order By: Relevance
“…2C and D). As we previously observed, the anti-PDGFR blots contained two bands representing the non-glycosylated and glycosylated forms of the receptors (7,24), while the anti-phospho-PDGFR blots possessed a single band representing the glycosylated, phosphorylated versions of the receptors upon ligand treatment (24).…”
Section: Pdgfra/b Heterodimers Dimerize Relatively Quickly and Have P...supporting
confidence: 72%
See 4 more Smart Citations
“…2C and D). As we previously observed, the anti-PDGFR blots contained two bands representing the non-glycosylated and glycosylated forms of the receptors (7,24), while the anti-phospho-PDGFR blots possessed a single band representing the glycosylated, phosphorylated versions of the receptors upon ligand treatment (24).…”
Section: Pdgfra/b Heterodimers Dimerize Relatively Quickly and Have P...supporting
confidence: 72%
“…PDGFRb homodimers via Dyngo-4a treatment resulted in increased phospho-ERK1/2 levels and decreased phospho-AKT levels at early timepoints of ligand stimulation (24), indicating that engagement of these signaling molecules occurs at the same subcellular platforms for PDGFRa/b heterodimers and PDGFRb homodimers. Alternatively, we previously observed that Dyngo-4a treatment of the PDGFRa homodimer cell line had a negative effect on ERK1/2 and AKT phosphorylation, resulting in delayed and reduced peaks of activation (24). These results demonstrated that rapid internalization of PDGFRa homodimers plays an important role in the propagation of downstream signaling and suggested that this dimer primarily signals from early endosomes.…”
Section: Relatedly Our Previous Results Demonstrated That Inhibition ...mentioning
confidence: 96%
See 3 more Smart Citations